Social and environmental impacts of traditional charcoal production: a case study in Hau Giang province, Viet Nam - Huynh Van, Thao; Huynh Cong Khanh,; Nguyen Cong Thuan,; Nguyen Duc Tai,; Nguyen Van Cong, (Vietnam Journal of Science and Technology, 2023)
This study investigated the status, environmental health risks and assessed contaminant concentrations of waste gases and ambient air quality in traditional charcoal production kiln areas in Hau Giang province. In total, 284 charcoal producers, 160 charcoal workers and 160 neighbors were interviewed using structured questionnaires. Additionally, Carbon monoxide (CO), nitro dioxide (NO2), total suspended particles (TSP), and sulfur dioxide (SO2) from traditional kilns and ambient air samples were analyzed. The result show that the number of kilns owned by each charcoal producer was 3.13 kilns per household; of which the average volume of each kiln was 59.07 m3 kiln-1, with a yearling charcoal yield of around 80.71 ton kiln-1. The profitability of charcoal producers was annually approximately 133 million VND per household. Charcoal workers predominantly reported suffering from eye irritation issues (41.6%) whilst adjacent neighbors frequently experienced respiratory problems (87.5%). The interviewees obviously recognized the negative impacts of charcoal production activities on community health (63.1% respondents) and local fruit farmers (79.4% respondents), yet only the minority of residents (8.11% respondents) required a change from the current charcoal-based livelihood. The CO, TSP, and SO2 in waste gas compositions all exceeded the maximum permissive levels of the Vietnamese National Standard (QCVN 19:2009/BTNMT), while the air quality surpassed the safety level of TSP and SO2 (QCVN 05:2013/BTNMT). This indicates very high risk to those who are regularly exposed to the air pollutants. The study suggested that technological solutions and responsible policies should be enforced to promote the sustainability of charcoal production and minimize the negative impacts on human health and the environment.